John Cassian, The Conferences - John Cassian approximately 360-approximately 435.; Boniface Ramsey (tr) (New York : Newman Press, 1997)
"John Cassian: The Conferences is the first complete English translation of the twenty-four dialogues between Cassian and the desert fathers of Egypt. A native of Dacia, Cassian (c. 360-430) joined a monastery in Bethlehem when he was in his early adult years. From Palestine, Cassian and Germanus, a companion, traveled several times to Egypt where they learned about the monastic tradition from the great desert masters or abbas. Cassian's writings here record twenty-four dialogues with fifteen abbas." "The Conferences have long been a key work in monastic circles and among scholars of spirituality. Ramsey's helpful introductions and annotations make them accessible to a new and broader readership. Careful attention to references, notes and appendices demonstrate the outstanding research and writing which helped produce this monumental volume."--BOOK JACKET.
Keywords: Patristics (3Yde GdBHGFjGJs; Monastic and religious life -- Early works to 1800.; Spiritual life -- Christianity -- Early works to 1800.; Asceticism -- Early works to 1800.